2023
DOI: 10.1111/tran.12603
|View full text |Cite
|
Sign up to set email alerts
|

Here, there, everywhere: The relational geographies of chemsex

Abstract: I laugh when guys on Grindr tell me 'I don't do drugs', then we meet and they get high as shit. (Gab,(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45) London, personal interview)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…The experience of abuse and HIV led RD to feel like a ‘complete failure’ (a term used several times across the interviews) towards his family and friends. Despite a precarious job and a modest income, he convinced himself that buying a house through a mortgage would have given him some sort of social redemption, making him more responsible, especially towards sexualized drug use (years before the panic discourse around the ‘chemsex epidemic’, see Stuart, 2013; for a geographical analysis of chemsex, see Di Feliciantonio, 2023). Critical scholarship in human geography has shown how indebtedness (which homeownership increasingly relies on) ‘is immediately subjective , i.e.…”
Section: A Life Shaped By Crises: Rdmentioning
confidence: 99%
“…The experience of abuse and HIV led RD to feel like a ‘complete failure’ (a term used several times across the interviews) towards his family and friends. Despite a precarious job and a modest income, he convinced himself that buying a house through a mortgage would have given him some sort of social redemption, making him more responsible, especially towards sexualized drug use (years before the panic discourse around the ‘chemsex epidemic’, see Stuart, 2013; for a geographical analysis of chemsex, see Di Feliciantonio, 2023). Critical scholarship in human geography has shown how indebtedness (which homeownership increasingly relies on) ‘is immediately subjective , i.e.…”
Section: A Life Shaped By Crises: Rdmentioning
confidence: 99%
“…The importance of research regarding the links between health, gender, and sexuality would appear to be both self-evident and vital. After all it is well understood that certain groups with same-sex desire are often at increased risk of various health-related concerns, including sexually transmitted infections especially among men – a topic that has remained relatively dominant in the field (Brown 1995, 1997; Brown and Di Feliciantonio 2022; Brown and Knopp 2010, 2014; Catungal et al, 2021, 2023; Kearns 2016; McKinnon et al, 2017; Myers 2010; Tucker 2020; Wilton 1996). Furthermore, it is understood that health concerns related closely to place-specific and yet complex, intersectional, and varied experiences of homoprejudice and gender-based violence and injustice remain a key set of challenges to overcome across the life-course (Datta 2016; Davies et al, 2018; Dyck 2003; Fluri and Piedalue 2017; Lewis 2009, 2014; Mkhize and Maharaj 2021; Sothern and Dyck, 2010; Sweet and Ortiz Escalante 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also shown that chemsex practices vary among different places and communities, influencing the choice of drugs used and the specific sexual practices involved. Cultural, social, and demographic factors can contribute to variations in chemsex practices, such as the availability and preferences for certain drugs, local norms and attitudes toward drug use and sexuality, and the influence of peer networks [9]. While the term "chemsex" was originally coined to describe a specific phenomenon within the MSM population, recent studies, drawing from clinical data, have expanded the use of the term to incorporate populations of various sexual orientations.…”
Section: Introductionmentioning
confidence: 99%